2005
DOI: 10.1093/brain/awh398
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex excitability in focal epilepsies not including the primary motor area--a TMS study

Abstract: It is unclear whether focal epilepsies chronically influence the processing of cortex distant to the epileptogenic zone. Therefore, motor cortex excitability was analysed in patients with temporal and extratemporal epilepsies whose epileptogenic zones did not include the primary motor area. Single and paired-pulse transcranial magnetic stimulation (TMS) was applied to the primary motor cortex in 20 healthy controls and 23 patients with focal epilepsy (39.4 +/- 13.2 years; 12 left, 11 right; 14 temporal, nine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
64
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 26 publications
9
64
0
2
Order By: Relevance
“…The enhanced responses to electrical stimulation in epileptogenic cortex were taken as indication of an increased excitability of neural tissue in these areas. Similarly, studies using TMS consistently reported a hyperexcitability in focal epilepsies (7)(8)(9)(10). Consequently, changes in excitability have been helpful in identifying the seizure focus before resective surgery.…”
mentioning
confidence: 93%
“…The enhanced responses to electrical stimulation in epileptogenic cortex were taken as indication of an increased excitability of neural tissue in these areas. Similarly, studies using TMS consistently reported a hyperexcitability in focal epilepsies (7)(8)(9)(10). Consequently, changes in excitability have been helpful in identifying the seizure focus before resective surgery.…”
mentioning
confidence: 93%
“…Other parameters such as ICI, ICF and cortical silent period (CSP) have been investigated in patients with focal epilepsy as well. Changes seem to be present not only in the ipsilateral but also in the contralateral motor cortex [13,21,46]. IHI has so far not been investigated in detail in patients undergoing surgical removal of the epileptic focus.…”
Section: Introductionmentioning
confidence: 99%
“…With transcranial magnetic stimulation (TMS) main mechanisms of cortical excitability, cortical representation of different muscles (Pascual-Leone et al, 1994), and the pathophysiology of neurological diseases, for example, epilepsy (Hamer et al, 2005), dystonia (Siebner et al, 1998) or PD (Priori et al, 1994), have been previously investigated. Furthermore, the influence of CNS-related drugs with a well-known mode of action was evaluated and differentiated from pathophysiological changes of the disease itself (Liepert et al, 1997;Ziemann et al, 1996a).…”
Section: Introductionmentioning
confidence: 99%